تأثير مواعيد الزراعة على بعض الصفات الفينولوجية وإنتاجية الفول السوداني ( Arachis Hypogaea) من البذور كما ونوعا - محمد, يوسف; عدلة, وسيم; يوسف, سوار (Latakia University Journal -Biological Sciences Series, 2018)
This research was conducted during 2016 growing season in A- sanowbar village belonging to Lattakia City to study the effect of planting date on the phonological stage of peanut plants calculated in Day unit, and its effect on plant seed productivity calculated in g/plant, and then seed production in Hectare (Kg/h) and percentage of protein and oil content in seeds. In this study three planting date have been studded, which were 20 April, 30 April and 10 May. Experiment was disined using Randomized Sectors in three replicates for each planting date. Results showed that: Planting in 10Th of May has shown significant deference compared to other planting date (30 April and 20 April) in early reaching flowering stage (28.60, 30.45, and 32.48 days) and maturation stage (134.9, 136.7, and 138.5 days). Planting in 20Th of April was better than others (30 April and 10 May) and seed production were 53.5. 49.8 and 45.8 g/plant, whereas were 3360.5, 3128.5 and 2879.2 Kg/H as production per area unit. Proteins in seeds were 32.25, 31.16 and 30.23 % in plants planted in 20Th of April, and the percentage of oil in these seeds were 43.875, 43.125 and 42.05 %. نفذ البحث في الموسم الزراعي 2016في قرية الصنوبر التابعة لمحافظة اللاذقية لبيان تأثير مواعيد الزراعة على مدة الاطوار الفنيولوجية لنبات الفول السوداني مقدرة باليوم وكذلك لمعرفة تأـثيرها على انتاجية نبات الفول السوداني من البذور على مستوى النبات الواحد مقدرة (غ/نبات) وعلى مستوى الهكتار الواحد مقدرة (كغ / هـ) وكذلك معرفة تأثيرها على النسبة المؤية للبروتين والزيت في البذور حيث تم استخدام ثلاثة مواعيد للزراعة (20نيسان – 30نيسان – 10أيار) وصممت التجرية بطريقة القطاعات العشوائية وبثلاث مكررات لكل موعد زراعة أظهرت النتائج تفوق نباتات الموعد الثالث (10أيار) تفوقا معنويا على نباتات موعد(30نيسان) وعلى نباتات الموعد الاول (20نيسان)في صفة التبكير بالوصول الى مرحلة الأزهار حيث بلغت على التوالي : (28.6-30.45-23.48يوم) وكذلك في مرحلة النضج حيث بلغت على التوالي: (134.9-136.7-138.5يوم) وتفوقت نباتات الموعد الأول (20نيسان)على نباتات الموعد الثاني (30نيسان) وعلى نباتات الموعد الثالث (10أيار) بانتاجية البذور على مستوى النبات الواحد حيث بلغت على التوالي:(53.5-49.8-45.8غ/نبات) وكذلك على انتاجية وحدة المساحة حيث بلغت على التوالي : (3360.5-3128.5-2879.2كغ/هـ) وكذلك في النسبة المؤية للبروتين في البذور حيث بلغت على التوالي:(32.25-31.16-30.23%) وكذلك في النسبة المؤية للزيت في البذور حيث بلغت على التوالي: (43.875-43.125-42.150%)